ADVOCACY TOOLS FREE USE ON EDUCATIONAL PERFORMANCE: STUDENT PERSPECTIVE IN COURSES OF SUSTAINABLE TOURISM IN THE UNED-CR (Revista Electrónica Calidad en la Educación Superior, 2016)
The research was conducted in order to identify the potential impact as well as systematize the experience of using tools for free use in educational processes in the context of distance education in the Department of Sustainable Tourism during the period of II-2015 for the purpose of documenting these processes and experience to other instances feedback and improve internal processes teaching regarding towards the individual student UNED. The questionnaire was the main instrument used for data collection, which was analyzed from the perspective of an exploratory research, based on the technique of case study, considering as a specific field experience of the Chair, which will expand the descriptions and dynamics generated in the process of the subject matter. The main conclusion indicates that incorporating free use tools allows greater access to learning materials effectively and efficiently. It also allows the creation of more favorable environments for learning in order to have good access to thematic content and communication processes with either their peers or teachers.